Réponses

2014-09-06T15:02:27+02:00
A = 1/2 + 3/4 - 5/6
A = 1 x 6 / 2 x 6 + 3 x 3 / 4 x 3 - 5 x 2 / 6 x 2
A = 6/12 + 9/12 - 10/12
A = 6/12
A = 6 x 1 / 6 x 2
A = 1/2

B = 40/9 - (4/3 - 2/9)
B = 40/9 - (4 x 3 / 3 x 3 - 2/9)
B = 40/9 - (12/9 - 2/9)
B = 40/9 - 10/9
B = 30/9
B = 3 x 10 / 3 x 3
B = 10/3

C = 2 - (3/2 - 1/4)
C = 2 - (3 x 2 / 2 x 2 - 1/4)
C = 2 - (6/4 - 1/4)
C = 2 - (5/4)
C = 2 x 4 / 1 x 4 - 5/4
C = 8/4 - 5/4
C = 3/4

D = (7/10 - 1/4) - (3/5 - 3/4)

D = (7 x 2 / 10 x 2 - 1 x 5 / 4 x 5) - (3 x 4 / 5 x 4 - 3 x 5 / 4 x 5)
D = (14/20 - 5/20) - (12/20 - 15/20)
D = 9/20 - (- 3/20)
D = 9/20 + 3/20
D = 12/20
D = 4 x 3 / 4 x 5
D = 3/5